Results of a patient-oriented second opinion program in Germany shows a high discrepancy between initial therapy recommendation and second opinion - Weyerstraß, Jan (BMC Health Serv Res, 2020)
BACKGROUND: As of 2015, second opinions are legally implemented in Germany. However, empirical results from German second opinion programs are lacking. The aim of this study was to examine several aspects within a population of a German second opinion program. METHODS: Study population consisted of patients who sought a second opinion in the period from August 2011 to December 2016. Multivariate logistic regression and ANOVA were used to examine differences in patient characteristics, differentiated by agreement of initial therapy recommendation and second opinion. Follow-up points for patient satisfaction and HRQoL were defined at 1, 3 and 6 months after obtaining the second opinion. RESULTS: Total number of patients who sought a second opinion was 1414. Most common indications concerned the knee (37.3%), spine (27.3%), hip (11.5%) and shoulder (10.1%). The independent specialists did not confirm the initial therapy recommendations in two out of three cases. The type of indication influenced the agreement between initial therapy recommendation and the second opinion significantly (p = 0.035). The second opinion and the offered service was highly valued by the patients (89%). CONCLUSIONS: The second opinion offers patients the possibility to confirm a medical indication independently and support patients in their decision making process. Reasons for the large discrepancy between initial therapy recommendation and second opinion should be addressed in future research.